FEATURES OF PHYSICAL EDUCATION CLASSES WITH STUDENTS OF SPECIAL MEDICAL GROUPS - Tatyana Denshikova; Hasan Arov; Konstantin Marinchenko; Irina Taran; Alexander Kudrya (Вестник Северо-Кавказского федерального университета)
The article is devoted to the study of the application in the educational process of the country's higher education institutions of a system of individual homework assignments for self-regulation for students of special medical groups that will ensure the successful fulfillment of the academic load in accordance with the plans for training specialists, students who are free from physical training for health reasons and who do not attend health education classes.